Light and electron microscopy characteristics of the muscle of patients with SURF1 gene mutations associated with Leigh disease - Pronicki, M (BMJ Publishing Group, 2008)
AIMS: Leigh syndrome (LS) is characterised by almost identical brain changes despite considerable causal heterogeneity. SURF1 gene mutations are among the most frequent causes of LS. Although deficiency of cytochrome c oxidase (COX) is a typical feature of the muscle in SURF1-deficient LS, other abnormalities have been rarely described. The aim of the present work is to assess the skeletal muscle morphology coexisting with SURF1 mutations from our own research and in the literature. METHODS: Muscle samples from 21 patients who fulfilled the criteria of LS and SURF1 mutations (14 homozygotes and 7 heterozygotes of c.841delCT) were examined by light and electron microscopy. RESULTS: Diffuse decreased activity or total deficit of COX was revealed histochemically in all examined muscles. No ragged red fibres (RRFs) were seen. Lipid accumulation and fibre size variability were found in 14 and 9 specimens, respectively. Ultrastructural assessment showed several mitochondrial abnormalities, lipid deposits, myofibrillar disorganisation and other minor changes. In five cases no ultrastructural changes were found. Apart from slight correlation between lipid accumulation shown by histochemical and ultrastructural techniques, no other correlations were revealed between parameters investigated, especially between severity of morphological changes and the patient’s age at the biopsy. CONCLUSION: Histological and histochemical features of muscle of genetically homogenous SURF1-deficient LS were reproducible in detection of COX deficit. Minor muscle changes were not commonly present. Also, ultrastructural abnormalities were not a consistent feature. It should be emphasised that SURF1-deficient muscle assessed in the light and electron microscopy panel may be interpreted as normal if COX staining is not employed.